Adherence to Singapore 24-hour Integrated Activity Guidelines and Quality of Life among Singaporean Children and Adolescents in the COVID-19 Pandemic (ACPES (ASEAN Council of Physical Education and Sport) in cooperation with Universitas Negeri Semarang (UNNES), 2022)
This study aimed to examine the prevalence of children and adolescents in meeting The Singapore Integrated 24-Hour Activity Guidelines for Children and Adolescents and whether the number of guidelines met was associated to Quality of Life (QoL). Parents of youths aged 7 to 18 years completed an online questionnaire consisting of the Singaporean Children Lifestyle Questionnaire and the Pediatric Quality of Life (PedsQL™) 4.0 Inventory. Parents reported on the physical activity (PA), sedentary behaviour (SB), recreational screen time (ST), sleep, dietary habits, as well as the QoL of their children. Their responses were benchmarked against the Singapore Integrated 24-Hour Activity Guidelines. Survey results of 181 youths showed that more than 38% of children and adolescents did not meet any of four guidelines relating to PA, recreational ST, sleep, and diet. Daily moderate-to-vigorous PA (31.1 vs. 17.1 min) and ST (3.5 vs. 2.5 h) of adolescents were significantly higher than that of children (p <.05) while adolescent sleep was significantly lower than that of children (7.3 vs 8.5 h, p < .05). QoL scores were higher when more guidelines were met but the association was not statistically significant (p = .11). Ameliorative programmes to help more youths cultivate positive lifestyle habits are recommended.